PENERAPAN TEORI PEMBELAJARAN IQRO’ DALAM PENGENALAN HURUF HIJAIYAH KEPADA ANAK DI MADIN AS-SALAM - Gus Romi Ahfad; Ismail (LPPM IAD Probolinggo, 2025)
This study aims to describe in depth the application of the Iqro' learning theory in the process of introducing hijaiyah letters to children at Madrasah Diniyah As Salam. The learning theory used in the Iqro' method emphasizes an individual approach and gradual learning that is in accordance with the level of development of early childhood. In the context of Islamic education, especially in learning to read the Qur'an, mastery of hijaiyah letters is the main foundation that children must have. Therefore, the right method is needed so that the learning process can take place effectively and efficiently. Keywoard : Learning Theory, Iqro' Method, Hijaiyah Letters, Children, Madrasah Diniyah